The role and rules of therapeutic education in patients with hypertension and diabetes in primary care - Zozulińska, Dorota; Wierusz-Wysocka, Bogna (Przewodnik Lekarza/Guide for GPs, 2007)
The care provided to patients with diabetes and hypertension mainly takes place in primary care practice. Individuals with diabetes and hypertension should be under particularly attentive care due to the high risk of cardiovascular disease events. The clinical and epidemiological data show that only 30% of patients meet the goals of treatment. One of the reasons for this status is insufficient knowledge about the diseases. Education of patients plays a crucial role in the treatment of patients with chronic diseases. Well educated and motivated patients using self-monitoring and self-management have not only better quality of life and metabolic control but also higher chance for longer life.